Shifting Regulatory Paradigms: The Impact of Indonesia’s Job Creation Law on Migrant Worker Protection and the Role of State, Employers, and Labor Organizations (2020-2023) - Sahl, Dafiq Febriali; Kitana, Nurisha; Gracella, Clairen (Journal of Governance and Administrative Reform, 2025)
Abstract  This study examines the evolving production regime within the labor process of Indonesian migrant workers, focusing on regulatory transitions from the 2017 Law on the Protection of Indonesian Migrant Workers (PPMI Law) to the Job Creation Law (2020–2023). It addresses persistent structural challenges confronting migrant workers and investigates the shifting power relations among labor, the state, and employers in managing these challenges. Based on in-depth interviews and a comprehensive review of relevant literature, the study identifies key structural constraints experienced by workers, the transformation of labor governance, the responses of labor organizations, and the structural power exercised by business actors. The findings indicate that Indonesian migrant workers are increasingly subject to complex structural vulnerabilities, stemming from a regulatory shift from state-centered protection under the PPMI Law to a market-oriented governance framework advanced by the Job Creation Law. A defining feature of this transition is the debureaucratization of migrant worker placement, signifying a broader alignment with neoliberal labor market principles. Business associations, particularly the Indonesian Migrant Worker Placement Companies (P3MI), have played an influential role in shaping this regulatory transformation through both structural and instrumental power. Conversely, labor organizations have resisted the commodification of migrant labor, advocating for the preservation of protective mechanisms. The study concludes that the reconfiguration of the regulatory framework governing Indonesian migrant workers results from the dynamic interplay of labor, state, and employer interests. The oscillation between protectionist and market-oriented regulatory models illustrates the contested nature of labor governance. By situating these developments within broader power structures, the study contributes to a nuanced understanding of the structural challenges shaping transnational labor migration from Indonesia. Keywords: Indonesian migrant workers; regulatory politics; employers; the state. Abstrak  Penelitian ini bertujuan untuk menelaah pergeseran rezim produksi dalam proses kerja buruh migran Indonesia akibat perubahan regulasi dari UU PPMI tahun 2017 ke UU Cipta Kerja (2020-2023). Penelitian ini mengangkat permasalahan struktural yang dihadapi oleh buruh migran Indonesia dan relasi antara buruh, negara, dan pengusaha yang berkaitan dalam persoalan struktural tersebut. Dengan menggunakan teknik wawancara mendalam dan studi literatur kami memetakan permasalahan struktural yang dialami buruh migran Indonesia, pergeseran paradigma produksi, respon organisasi-organisasi buruh, dan kekuatan struktural kelompok bisnis. Hasil penelitian ini menemukan adanya persoalan struktural yang begitu kompleks dihadapi oleh buruh migran Indonesia di tengah pergeseran paradigma produksi dari berbasis perlindungan oleh birokrasi dan negara pada UU PPMI tahun 2017 menjadi berbasis pada kepentingan pasar dan debirokratisasi perusahaan jasa penempatan buruh migran yang tercermin dalam UU Cipta Kerja. Penelitian ini juga menguraikan praktik kekuatan struktural serta instrumental kelompok asoasi bisnis (P3MI) dalam pergeseran paradigma regulasi, dengan perlawanan oleh kelompok buruh yang menolak paradigma regulasi berbasis pasar yang ada dalam UU Cipta Kerja. Kesimpulannya, secara faktual dari kekuatan buruh, negara, dan pengusaha telah saling mempraktikkan kekuasaannya dan kepentingannya satu sama lain yang berdampak pada paradigma regulasi proses kerja buruh migran Indonesia antara UU PPMI tahun 2017 dan UU Cipta Kerja. Penelitian ini berimplikasi terhadap penjelasan persoalan struktural yang dihadapi oleh buruh migran Indonesia dalam kaitannya dengan tarik-menarik kepentingan regulasi serta reduksi-amplifikasi peran antara negara, buruh, dan pengusaha. Kata kunci: buruh migran Indonesia; politik regulasi; pengusaha; negara.